VIRTUAL ENVIRONMENTS AND SIMULATIONS IN ROBOTICS TEACHING - Zhabayev Е.Х.; Revshenova М.И. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
The article is devoted to existing approaches, virtual environments and simulators in robotics. Robotics is one of the important areas that are being implemented in educational institutions of Kazakhstan. Robotics provides a unique opportunity to stimulate students’ interest in science, technology, engineering and mathematics (STEM) and develop their skills in programming, problem solving, and creative thinking. It also helps students develop teamwork, problem thinking, creativity and innovation skills. To teach robotics, you can use virtual environments and simulators, software tools that allow you to simulate and simulate the work of robots in a virtual environment. Students can program and test their virtual skills. Some popular virtual environments and simulators used in robotics training are given, in particular, Gazebo, Webots, V-REP (Virtual Robot Experiment Platform), Robot Mesh Studio, RoboBlockly, Open Roberta Lab. The features and capabilities of these virtual environments and simulators are highlighted.